2003
DOI: 10.1046/j.1365-2249.2003.02205.x
|View full text |Cite
|
Sign up to set email alerts
|

Gliadin, endomysial and thyroid antibodies in patients with latent autoimmune diabetes of adults (LADA)

Abstract: SUMMARYLatent autoimmune diabetes of adults (LADA) manifested after the age of 35 is characterized by the presence of disease-specific autoantibodies (anti-glutamate decarboxylase GADAb, anti-IA2Ab). However, autoimmunity in Type 1 diabetes mellitus is not targeted only to pancreatic beta-cells. No data have so far been published concerning the antibodies associated with other autoimmune disease in LADA patients. The presence of anti-thyroglobulin (TGAb), anti-thyroid peroxidase (TPOAb), antigliadin IgA (AGAAb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 37 publications
6
29
1
1
Order By: Relevance
“…The frequent association between celiac disease and other autoimmune diseases, particularly type 1 diabetes (T1D) and thyroiditis, suggests that celiac enteropathy shares certain pathogenic mechanisms with other autoimmune diseases. 80 Indeed, gut mucosal barrier dysfunction was repeatedly demonstrated and confirmed by genetic studies in patients with celiac disease and T1D. [81][82][83] Several intestinal viral triggers including adenovirus, hepatitis C virus, and rotavirus and bacterial infections capable of initiating or augmenting gut mucosal responses to gluten were suggested to play a role in the pathogenic mechanism of this disease.…”
Section: Celiac Diseasementioning
confidence: 99%
“…The frequent association between celiac disease and other autoimmune diseases, particularly type 1 diabetes (T1D) and thyroiditis, suggests that celiac enteropathy shares certain pathogenic mechanisms with other autoimmune diseases. 80 Indeed, gut mucosal barrier dysfunction was repeatedly demonstrated and confirmed by genetic studies in patients with celiac disease and T1D. [81][82][83] Several intestinal viral triggers including adenovirus, hepatitis C virus, and rotavirus and bacterial infections capable of initiating or augmenting gut mucosal responses to gluten were suggested to play a role in the pathogenic mechanism of this disease.…”
Section: Celiac Diseasementioning
confidence: 99%
“…A high frequency (19%) of antibodies to gliadin was reported in LADA [44], but the prevalence of coeliac disease confirmed by biopsy is unknown. An increased frequency of antibodies to 21-hydroxylase and 17-hydroxylase, markers of autoimmune hypoadrenalism (Addison's disease), has also been reported in LADA [43].…”
Section: Autoimmune Disease Associationsmentioning
confidence: 99%
“…The phenomenon of recruitment of additional T cell epitopes has been reported. 12 The presence of obesity is not incompatible with diagnosis of immune mediated diabetes. Studies report a mean BMI in the overweight category (BMI >25.0 kg/m 2 ) in a LADA population of European extraction.…”
Section: Commentmentioning
confidence: 99%
“…12 The prevalence of thyroid antibodies in adult patients with type 1 diabetes has been reported to be between 20-30%. A recent study showed the presence of thyroid peroxidase antibodies in LADA (22.1%) differed significantly to type 2 diabetes (9.4%), whereas no significant difference was found in the presence of thyroglobulin antibodies.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation